PENGARUH ENVIRONMENTAL PERFORMANCE DAN ENVIRONMENTAL COSTS TERHADAP PROFITABILITAS PERUSAHAAN MELALUI CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Gusnadi, Dhia Hasna Rahmadhani; Nurhadi, Nurhadi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Company activities certainly have an impact on the environment, therefore companies are required to apply a sustainable business concept, the Triple Bottom Lines. The application of the triple bottom lines, especially in terms of environmental protection (planet) assesses how companies can generate profits and can also minimize negative impacts on the environment. This study aims to examine the effect of environmental performance and environmental costs on company profitability through environmental disclosure. The sampling method used purposive sampling with 25 samples of consumer goods companies listed on IDX 2019 – 2021. This study used linear regression analysis to test the research hypothesis. The results of the hypothesis test prove that environmental cost has a significant effect on corporate social responsibility disclosure, but environmental performance has no significant effect. Meanwhile, environmental cost and corporate social responsibility disclosure have a significant effect on company profitability, but environmental performance has no significant effect. Path analysis found that corporate social responsibility disclosure bridges the effect of environmental cost variables on company profitability, but is unable to bridge the effect of environmental performance on company profitability.